Chemical food safety - Brimer, Leon (Modular texts, 2011)
Preventing contamination with problematic chemical compounds in food requires an understanding of how they can enter and pass along the food production and processing chain, as well as relevant issues in toxicology and risk management. This book covers the basic and applied science needed to understand, analyse and take professional action on problems and questions concerning chemical food safety that call for interventions on a local, regional, national or international level. Risk assessment is explained in the context of targeted future risk management and risk communication. The book also follows food contaminants through production and processing of foods of plant, fungal, algal or animal origin, including oral exposure and intestinal absorption of such contaminants, with a view to assessing, managing and communicating risk in the food chain